(untitled) (Theatrum historiae, 2025)
This study explores the first twenty-three years of the life of Božena Vavrečková (later Havlová). She was the daughter of the diplomat and Baťa company director Hugo Vavrečka and later became the wife of the prominent Prague entrepreneur Václav M. Havel. Although her later life has been noted, it was mostly in relation to her sons or husband. The early period of her life has not been sufficiently examined. This study focuses on these formative years. It reconstructs her life from early childhood and adolescence, through to her marriage and the birth of her first son, Václav Havel – with this event, a new era in her life begins. The research pays particular attention to the social, cultural, and familial environments that influenced Božena’s life, her education, and her worldview. It examines her upbringing in an intellectually and socially privileged family, as well as her several changes of residence. It also highlights the emergence of her interests and inclinations. The study draws on a broad range of sources, including archival records, personal correspondence, official documents, and contemporary periodicals. This combination of materials allows for a nuanced reconstruction of Božena’s early life. The study aims to shed light on what her early life looked like, how it was shaped by her surroundings, and how it contrasts with idealised later portrayals.